Analyzing Renewable and Nonrenewable Energy Sources for Environmental Quality: Dynamic Investigation in Developing Countries. (21st September 2021) - Khan, Itbar; Han, Lei; Khan, Hayat; Kim Oanh, Le Thi
Abstract : Most of developing countries are facing environmental degradation challenges as these countries use energy from fossil fuels to enhance economic activities and that leads to environmental degradation. The use of renewable energy is required to mitigate environmental degradation; however, developing countries may not yet have reached the desired level to acquire renewable energy. It is important for developing countries to make polices to shift from nonrenewable energy to renewable energy use to protect environmental quality. In this regard, the importance of different energy sources and financial development in enhancing environmental quality in 21 developing countries is examined from 1970 to 2018. The study employed dynamic estimator, and the results indicate that the sources of renewable energy enhance environmental quality as compared to nonrenewable energy and its sources. Financial development also lowers environmental quality in our results. The study recommends reducing carbon emissions by reducing the use of fossil fuel energy and acquiring new technologies, attracting foreign investors in clean energy that provide clean technologies for green production, and investing in renewable energy sources to evade nonrenewable energy. Policy makers should adopt environmentally-friendly strategies and equipment to protect environmental quality, while striving for achieving economic growth.